1987
DOI: 10.1063/1.98763
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic two-dimensional surface-emitting arrays of GaAs/AlGaAs diode lasers

Abstract: Monolithic two-dimensional arrays with light emission normal to the surface have been obtained by fabricating edge-emitting quantum well GaAs/AlGaAs lasers with deflecting mirrors adjacent to both laser facets. The facets and mirrors were formed by ion beam assisted etching. Proton bombardment between adjoining lasers was used to prevent lasing in the transverse direction. At the highest pulsed current used in these experiments, 10.5 A, the power output of a 22-element array was 1.6 W, which corresponds to a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(4 citation statements)
references
References 24 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…This research idea was previously utilized by J. P. Donnelly et al, for the fabrication of monolithic 2D arrays based on GaAs/AlGaAs laser diodes, whereas vertical laser facets and deflecting mirrors were fabricated by ion beam-assisted etching [ 25 ]. Likewise, N. Hamao et al, reported SEL diodes based on GaAs/AlGaAs with 45° total reflection micro mirrors formed by Reactive Ion Etching (RIE) method within 1° of precision of 45° angle [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This research idea was previously utilized by J. P. Donnelly et al, for the fabrication of monolithic 2D arrays based on GaAs/AlGaAs laser diodes, whereas vertical laser facets and deflecting mirrors were fabricated by ion beam-assisted etching [ 25 ]. Likewise, N. Hamao et al, reported SEL diodes based on GaAs/AlGaAs with 45° total reflection micro mirrors formed by Reactive Ion Etching (RIE) method within 1° of precision of 45° angle [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the front surface of the deflector to be parabolic, etching a second-order polynomial curve IS necessary. power output of 16.5 W at 62 A, which corresponds to a power density of 1.5 kW/cm 2 [21,23,37,38].…”
Section: Monolithic Arrays With External Deflecting Mirrorsmentioning
confidence: 99%
“…Researchers are hopeful that monolithic arrays, which can be fabricated almost entirely with high-volume semiconductor processing techniques, will be more arnenable to mass production. As a possible direct replacement for hybrid arrays, monolithic two-dimensional arrays of GaAs/ AlGaAs diode lasers with light emission normal to the surface have been made by fabricating horiwntal-cavity edge-emitting quantum-well lasers coupled with external mirrors that deflect the radiation from the laser facets by 90°( Figure 22 [a]) [21,23,37,38]. In addition, several preliminary surface-emitting arrays with IBAE is a dry-etching technique in which the chemically reactant species and the energetic ions can be independently controlled.…”
Section: Monolithic Surface-emitting Diode Laser Arraysmentioning
confidence: 99%
See 1 more Smart Citation